«ОСТРЕЙШИЕ НОЖНИЦЫ ГЕНЕТИКИ» - ПРЫЖОК В БУДУЩЕЕ - Малахова, Анастасия Алексеевна; Котлов, Артём Андреевич; Васнецова, Алёна Степановна; Абдукаева, Нелли Сулеймановна; Косенкова, Наталия Сергеевна (FORCIPE, 2022)